Unacknowledged kinships: postcolonial studies and the historiography of Zionism - Vogt, Stefan (The Tauber Institute series for the study of European Jewry, 2023)
"A ground-breaking collection of essays regarding the history, implementation and challenges of using 'antisemitism' and related terms as tools for both historical analysis and public debate. A unique, sophisticated contribution to current debates in both the academic and the public realms regarding the nature and study of antisemitism today"--